EFFECT OF BAMBOO SUBSTRATE ON GROWTH AND PRODUCTION OF CLARIAS BATRACHUS (BLOCH) FINGERLINGS - SUGUMARAN, E.; RADHAKRISHNAN, M.V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Periphyton may be an alternative or a complement for supplemental feed in fingerling production. Growth and production of Clarias batrachus were evaluated in twelve 5x5xlm concrete mudbottomed tanks with bamboo poles for periphyton production. There were two densities of 1.5-m bamboo poles: 98 and 196 poles per tank. Parallel control groups were kept. Tanks were stocked with fingerlings (average weight 2.5 g) at 25 fish tank. Fish were harvested after 75 days. During the experiment, periphyton density on the substrates (ash-free dry matter (AFDM and ash) and Water quality were monitored regularly. Water quality was favourable for fish growth and there were only minor differences between the treatments. Periphyton biomass density on the substrates initially increased and was subsequently reduced during the experiment. Although more experiments are needed to optimize periphyton density in relation to fish size and stocking density, the results show that periphyton can replace or complement supplemental feeding due to the formation of bacterial biofilm in water for fingerling culture.